A tool for collaborative circular proposition design. (15th May 2021) - Brown, Phil; Baldassarre, Brian; Konietzko, Jan; Bocken, Nancy; Balkenende, Ruud
Abstract: Circular oriented innovation aims to address sustainability problems such as resource scarcity, pollution and climate change by (re)designing industrial products, processes, business models, and value network configurations. Although the literature identifies collaboration as crucial for circular oriented innovation—due to the complexity, risk and uncertainties involved—few tools have been developed to support it. To address this gap, we develop and test a tool that helps companies ideate to identify partners and value within circular oriented innovation. The tool integrates decision-making principles from the entrepreneurship theory of effectuation within a design thinking approach to stimulate collaborative ideation of circular propositions. We demonstrate and test the tool through six workshops, and collect data via observations, field-notes, assessment forms and user discussions. Our results show that: 1) users are receptive to visualisation and effectuation-based questions to collaboratively ideate circular propositions; 2) expert facilitation helps to maintain a circularity focus to avoid 'business-as-usual' ideas; and 3) differences in the maturity and scope of projects may influence the usefulness of the tool. We contribute to theory by demonstrating the integration of effectuation, design thinking, and lean experimentation approaches into a tool to advance circular oriented innovation. We contribute to practice with the tool itself that supports early and quick ideation to identify partners and perceived value. This supports companies to collaborate and advance the design of circular propositions that bring circular business model ideas closer to implementation.